History of Maqtal al-Hossein Documents: From Factual History to Fictional History - Khoirunnisa Muhammad (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
The chronological account of Maqtal al-Hossein is a literary work that has been preserved and has become a source of inspiration for the formation of the collective identity of the Shi'a. However, Maqtal al-Hossein as a literary work, written based on the subjective understanding of its author, also leaves traces of distortion in the writing of Maqtal al-Hossein itself. This article aims to illustrate the gradual shift of Maqtal al-Hossein's narrative from historical to fictional. This article discusses (1) A discussion of the history of the writing of Maqtal al-Hossein as a development of literacy by previous writers, followed by a review of the history of the writing of the historical kitab Maqtal al-Hossein from the second century to the writing of Maqtal al-Hossein in the tenth century Hijri. (2). A review of the critical analysis of the text of the hadiths of Maqtal al-Hossein that indicated fiction from the third century Hijri to the tenth century Hijri in the two kitabs of Maqtal al-Hossein in the third century and Maqtal al-Hossein in the seventh century Hijri. The conclusion of this article shows that the writing of Maqtal al-Hossein from the period of the third century Hijri to the tenth century Hijri provides an argument about the shift in the historical value of writing the history of Maqtal al-Hossein, from historical facts to fictional narratives. Meanwhile, the writing of Maqtal al-Hossein from the tenth century was also influenced by the various interests of Islamic power at that time.